Barite Precipitation on Suspended Organic Matter in the Mesopelagic Zone - Martinez-Ruiz, F.; Paytan, A.; Gonzalez-Muñoz, M. T.; Jroundi, F.; Abad, M. M.; Lam, P. J.; Horner, T. J.; Kastner, M. (Frontiers in Earth Science, 2020)
Mechanisms underlying barite precipitation in seawater and the precise depths of barite precipitation in the water column have been debated for decades. Here we present a detailed study of water column barite distribution in the mesopelagic zone at diverse stations in the open ocean by analyzing samples collected using multiple unit large volume in-situ filtration systems in the Pacific, Atlantic and Indian oceans. Our results demonstrate that barite is an organo-mineral particularly abundant at intermediate depths throughout the world’s ocean regardless of saturation state with respect to barite. This is confirming the notion of precipitation at depths of intense organic matter mineralization. Our observations further support the link between barite formation and microbial activity, demonstrated by the association of barite particles with organic matter aggregates and with extracellular polymeric substances (EPS). Evidence for microbial mediation is consistent with previous experimental work showing that in bacterial biofilms Ba binds to phosphate groups on cell surfaces and within EPS. This organo-accumulation promotes high concentrations of Ba leading to saturated microenvironments and nucleation sites favoring precipitation. The distribution of Ba isotopes in the water column and in particulate matter is also consistent with the proposed precipitation mechanism.